Rye–vetch residue quality and plastic mulch affect soil nitrogen dynamics in vegetable production systems - Hayden, Zachary D.; Ngouajio, Mathieu; Brainard, Daniel C. (Agronomy journal, 2023)
Cover crops can be an important source of nitrogen (N) for organic vegetable production, but N availability depends on the characteristics of the cover crop residues and crop management practices following termination. A 2‐year field experiment in Michigan investigated (1) how the proportion of cereal rye (Secale cereale L.) and hairy vetch (Vicia villosa Roth) sown in a cover crop mixture (seven treatments ranging from 100% rye to 100% vetch plus a no‐cover‐crop control) influences cover crop residue quantity and quality and (2) how rye–vetch residue characteristics and the use of black polyethylene mulch (PM) interact to affect soil N dynamics, crop quality, and yield in bell pepper (Capsicum annuum L.) and slicing cucumber (Cucumis sativus L.) production. Positive correlations among pepper marketable yield, leaf chlorophyll content (SPAD), and average soil inorganic N support that N fertility was a key driver of treatment effects. Higher sown proportions of vetch and the use of PM were generally associated with higher vegetable yields and soil N. The magnitude of yield response to PM was greater in a year with higher precipitation and greater for pepper than cucumber. Percentage of nonmarketable fruit decreased (pepper) and increased (cucumber) with PM. Pore water nitrate concentration below the root zone reflected plow layer N under PM but was more responsive to precipitation under bare ground. Our results demonstrate that PM can be an important tool for preserving N fertility benefits from high N cover crop residues for vegetable production, particularly on sandy soils. Core Ideas Cereal–legume cover crop mixture proportion and plastic mulch use in vegetable production were investigated. Shoot N increased and C:N decreased with higher vetch proportion in rye–vetch mixtures. Cover crop N positively correlated with vegetable yields and soil and pore water N. Plastic mulch increased soil N and yields while reducing N leaching potential from precipitation. Nonmarketable fruit decreased (pepper) or increased (cucumber) with black plastic mulch.